Hubungan Antara Subjective Well-Being dengan Burnout pada Guru Anak Berkebutuhan Khusus Selama Pandemi Covid-19 - Anissa Rizky Andriany; Ajheng Mulamukti Asih Pratiwi; Mahesti Pertiwi (Ridwan Institute, 2021)
The purpose of study was to analyze the work stress and the burn out of teachers of children with Special Needs during the pandemic Covid-19. This research uses a quantitative method with a type of correlational test research, which is a study used to find the relationship between two or more variables. Based on the results of the research, it was found that the level of subjective well-being on teachers of children with special needs during the Covid-19 pandemic was at a low level of 33.3%, while the moderate level of 35.5% and at the high level of 31.1%. The factors that influence subjective well-being consist of gender, goal, religion or spirituality, social relationship quality factors, personality. Based on the results of the research conducted, it can be concluded that subjective well-being is significantly correlated with burnout. There is a negative relationship between subjective well-being and burnout on teachers of children with special needs during the Covid-19 pandemic, namely the higher the subjective well-being, the lower the burnout and vice versa.